In Search of a “Newer and Truer” Literature: Thomas Phillips Thompson and The Labor Advocate - Buchanan, David (Papers of the Bibliographical Society of Canada / Cahiers de la Société bibliographique du Canada, 2023)
This article describes the uses of literature in The Labor Advocate: A Weekly Labor Reform Newspaper (Toronto, 1890-91). As editor of the Advocate, Thomas Phillips Thompson aimed to increase awareness of the means and consequences of industrial capitalism, and thus enhance the possibility of social justice for the working class. He did so in a mixed format periodical that included poetry, short fiction, and serialized novels as well as editorials, biographies, obituaries, reports, letters, and columns. Over forty-four issues, Thompson experimented with literary expression to attract readers and foster the democratic reform of social organization. Analysis of the Advocate points to the importance of communication strategies in both the early history of the Canadian labour press and the longer history of labour in transnational contexts.